Analisis mobilitas pembawa muatan pada lucutan plasma korona negatif konfigurasi kawat silinder menggunakan gas nitrogen - BN Michael GP; Muhammad Nur (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Carbon mobility analysis has been carried out on plasma corona discharge of negative of cylindrical wire configuration using nitrogen gas. The study was conducted using a 24 cm long stainless steel cylinder and an iron wire stretched to the center in a cylindrical tube with a wire length of 24 cm. Both ends of the cylinder are closed using an insulator material and given the input and output holes of the gas. The nitrogen gas flowrate used is 2 L / min to 6 L / min at intervals of 1 L / min and the applied voltage is from 0 kV until arc discharges occur at 0.3 kV intervals. The characterization of the negative corona discharge plasma reactor was carried out to determine the initial stresses for the emergence of currents as a sign of the operation of the reactor, the final stresses for knowing arc discharges, reactor working areas, and the relation of currents to stress for gradient values. The result of this characterization is obtained by charge load mobility 4.59x10-1 m2/V.s at 2 L / min flowrate, 9.29x10-3 m2/V.s at flowrate 3 L / min, 1.15x10-1 m2/V.s at a flowrate of 4 L / min, 4.13x10-3 m2/V.s at a flowrate of 5 L / min, and 9.29x10-3 m2/V.s at a flowrate of 6 L / min. The result of this negative corona charge discharging mobility is compared with a positive corona discharge study. From this comparison it can be concluded that the mobility of negative corona discharge charge carriers at 2 L / min flow discharge is higher than positive discharge, while at 6 L / min flowrate the negative and positive corona charge discharge charge is equal. Keywords: Plasma corona negative, cylinder wire, charge carrier mobility, nitrogen gas, voltage, current